Engineering students' perception on learning through cooperative problem-based learning (CPBL) for the first time - Phang Abdullah, Fatin Aliah (2012)
Cooperative problem-based learning (CPBL) has been proven to be a powerful technique in engaging and developing students in learning, as well as a multitude of professional skills. Nevertheless, academic staff in engineering who are new to conducting CPBL may face difficulties because students who are also new to this inquiry based technique will normally be "traumatized" because of the drastic change in the learning environment and requirements. As part of a larger study on training and supporting academic staff in implementing CPBL, a phenomenological study was conducted on the categories of variations in students' perceptions towards learning as they go through a course that fully utilized CPBL in a whole semester. The main purpose is to identify students’ perception towards CPBL in two aspects: (1) perception and acceptance/rejection; and (2) the benefits and improvements gained along the learning process. The paper illustrates the extent of acceptance and effectiveness of CPBL for an engineering course taught by a lecturer who had undergone a series of training on cooperative learning and problem based learning, but is new to implementing CPBL. Through classroom observations, students’ self-reflection notes and interviews with students for one whole semester, the results are reported in three stages: (1) beginning of the semester; (2) in the middle the semester; and (3) at the end of the semester. Four types of initial-to-final students’ perspectives were found. The analysis of the interviews reveal that, first and foremost, it is essential for academic staff to understand and embrace the philosophy behind CPBL, which will enable them to provide students with appropriate support especially in developing team working, time management, learning and thinking skills. In addition, proper explanation and justification behind each step in the CPBL cycle, as well as the overall planning through the different problems, are also necessary to avoid confusion and cutting corners in learning among students. Most of all, the analysis reveal the importance of emotional support in the form of motivation and encouragement, as students go through various emotions that form into perception, which in turn affect their performance.